Improving The Ability of Writing News Text Through Learning Models TTW (Think Talk Write) - Susanti, Lia Dwi; Wardiah, Dessy; Fitriani, Yessi (Jurnal Pendidikan Tambusai, 2021)
The formulation of the problem in this study is: "Can the TTW (ThinkTalk Write) model improve the ability to write news texts for eighth grade students of SMP Negeri 1 OKU? The purpose of this study was to analyze and describe the improvement in the ability to write news texts for eighth grade students of SMP Negeri 1 OKU. The hypothesis in this classroom action research (PTK) is that "the TTW (Think Talk Write) learning model can improve the ability to write news for grade VIII students of SMP Negeri 1 OKU. The subjects in this study were 30 students of class VIII SMP Negeri 1 OKU in Indonesian. The object of this research is the application of the TTW (ThinkTalk Write) learning model to the material written as news texts in Indonesian language learning for class VIII SMP Negeri 1 OKU. Based on the results of the study, it was proven that the increase in writing news texts with the TTW (Think Talk Write) learning model in the first cycle an average of 62.87 students who achieved learning completeness were 6 students. In cycle II, the students' ability to write News Texts averaged 72.53. Students who achieved completeness in the learning process were 22 students. Thus, the increase was 53.33% from cycle I to cycle II..